Preparation method of Au-loaded zinc-tin oxide composite triethylamine gas sensor
The heterostructured Zn2SnO4/SnO2/ZnO composite material was prepared by hydrothermal method and loaded with Au nanoparticles, which solved the problems of low sensitivity and poor selectivity of existing zinc stannate-based triethylamine sensors, and achieved rapid triethylamine Responsive and high sensitivity detection.
Patent Information
- Application Number
- CN202210914348.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-08-01
AI Technical Summary
The existing zinc stannate-based triethylamine sensors have problems such as low sensitivity, long response/recovery time, high detection limit and poor selectivity.
The Zn2SnO4/SnO2/ZnO composite material with heterostructure was prepared by a one-step hydrothermal method, and Au nanoparticles were loaded by impregnation method to form the Au-loaded Zn2SnO4/SnO2/ZnO composite material.
It realizes rapid response to triethylamine at lower operating temperatures, improves the sensitivity and selectivity of the gas sensor, and lowers the detection limit.
Smart Images

Figure CN115290707B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of metal oxide semiconductor gas sensors, and in particular to a method for preparing a triethylamine gas sensor of an Au-loaded zinc-tin oxide composite material. Background technology:
[0002] Triethylamine (TEA) is a typical organic amine compound with a strong pungent odor. It is widely used as a catalyst, solvent, dye, and preservative. However, as a volatile organic compound (VOCs), the threshold concentration of TEA in the air is 10ppm. Long-term exposure to excessive TEA can cause a series of health problems, such as skin irritation, headache, gastroenteritis, pulmonary edema, and even death. In addition, TEA can be used as a marker to detect food quality. Therefore, effective detection and timely warning of TEA are very necessary.
[0003] Among various gas detection technologies, metal oxide semiconductor gas sensors have attracted widespread attention due to their advantages such as low price, small size, and easy integration. Its working principle is to detect gas by adsorbing gas on the surface of metal oxide semiconductor gas-sensitive materials or reacting with gas to cause changes in semiconductor resistance. At present, metal oxide semiconductor gas sensors used to detect TEA still have problems such as high operating temperature, low selectivity, and high detection limit. Among the methods to improve the performance of sensitive materials, constructing heterostructures can shorten the response time; using precious metal modification can improve sensitivity, reduce operating temperature, and even change selectivity.
[0004] In practical applications, it is difficult to achieve that the gas sensor has the characteristics of low operating temperature, fast response, sufficient sensitivity, high selectivity, low detection limit and good stability at the same time. Therefore, the present invention provides a preparation method of a gold-loaded zinc-tin oxide composite triethylamine gas sensor, the purpose of which is to improve the gas-sensitive properties of the gas sensor by constructing a heterogeneous structure and noble metal modification to overcome the shortcomings in practical applications. Summary of the invention:
[0005] The present invention aims at the shortcomings of the current zinc stannate-based triethylamine sensor, such as low sensitivity, long response / recovery time, high detection limit, poor selectivity, etc., and provides a method for preparing an Au-loaded zinc-tin oxide composite material, and applies it to the rapid detection of TEA gas. The method first prepares the base material Zn2SnO4 / SnO2 / ZnO by a one-step hydrothermal method, and successfully constructs a heterostructure; secondly, on the basis of this base material, Au nanoparticles are loaded by an impregnation method. In the loading process, excess sodium borohydride can completely reduce the gold, so that the Au nanoparticles are successfully attached to the surface of the material to form a Schottky contact. The element obtained by the present invention overcomes the problems of high operating temperature, low sensitivity, long response / recovery time, high detection limit, poor selectivity, etc. of the existing device, and realizes a rapid response to triethylamine at a relatively low operating temperature.
[0006] The technical solution of the present invention is:
[0007] A method for preparing an Au-loaded zinc-tin oxide composite triethylamine gas sensor, the method comprising the following steps:
[0008] (1) Add Zn(CH3COO)2·2H2O and C6H5Na3O7·2H2O to deionized water and stir for 5-10 min to obtain solution A.
[0009] Wherein, the molar ratio is Zn(CH3COO)2·2H2O:C6H5Na3O7·2H2O=1:0.5-1; 1-3 mmol Zn(CH3COO)2·2H2O is added to every 8-12 mL of deionized water;
[0010] (2) Dissolve SnCl4·5H2O in anhydrous ethanol and stir for 5-10 min to obtain solution B; add 0.5-1.5 mmol SnCl4·5H2O for every 4-6 mL of anhydrous ethanol;
[0011] (3) under the action of magnetic stirring, solution A and solution B are mixed and stirred for 10 to 20 minutes to obtain solution C; wherein the molar ratio of Zn(CH3COO)2·2H2O to SnCl4·5H2O is 2:1 to 3;
[0012] (4) dropping NaOH solution into solution C and stirring for 20 to 50 minutes; wherein the molar ratio of NaOH to Zn(CH3COO)2·2H2O and SnCl4·5H2O is 6 to 10:2:1 to 3; and each 20 to 30 mL of NaOH solution contains 5 to 15 mmol of NaOH;
[0013] (5) transferring the solution obtained in step (4) into a stainless steel autoclave lined with polytetrafluoroethylene, sealing it, keeping it in an oven at 180-200° C. for 14-18 hours, cooling it naturally to room temperature, washing it alternately with deionized water and anhydrous ethanol, and then drying it at 60-80° C. for 3-10 hours to obtain a powder material;
[0014] (6) annealing the material obtained in step (5) at 600-800° C. for 0.5-2 h at a heating rate of 2-5° C. / min, and then naturally cooling to room temperature to obtain a Zn2SnO4 / SnO2 / ZnO composite material;
[0015] (7) adding the Zn2SnO4 / SnO2 / ZnO composite material to deionized water, and then ultrasonicating at a power of 200 to 300 W for 8 to 15 minutes to obtain a reaction solution; adding 25 to 50 mg of the Zn2SnO4 / SnO2 / ZnO composite material to every 10 to 20 mL of deionized water;
[0016] (8) adding chloroauric acid solution to the solution of step (7) and stirring magnetically for 8 to 15 minutes;
[0017] Wherein, the mass ratio of chloroauric acid to the Zn2SnO4 / SnO2 / ZnO composite material contained in step (7) is 1:10-200;
[0018] The concentration of the chloroauric acid solution is 0.015-0.025 g / mL;
[0019] (9) Adding the sodium borohydride solution to the solution of step (8), stirring for 2 to 5 hours, washing with deionized water and anhydrous ethanol alternately, and then drying at 60 to 80° C. for 3 to 10 hours; wherein the molar ratio of sodium borohydride to chloroauric acid is 1 to 15:1.
[0020] (10) placing the material obtained in step (9) in a muffle furnace, annealing at 350-500° C. for 1-3 h, and then naturally cooling to room temperature to obtain an Au-loaded Zn2SnO4 / SnO2 / ZnO composite material;
[0021] (11) The composite material obtained in step (10) is prepared into a paste with deionized water and coated on the surface of the ceramic tube; wherein the coating thickness is 10 to 20 μm and the solid-liquid ratio is 8 to 12 mg:20 μL;
[0022] (12) placing the ceramic tube coated with the gas-sensitive material under a drying lamp for 5 to 10 minutes, placing it in a muffle furnace after drying, annealing it at 350 to 800° C. for 0.5 to 2 hours, with a heating rate of 2 to 5° C. / min, and then cooling it naturally to room temperature; passing a nickel-chromium alloy heating coil with a resistance value of 30 to 40 Ω through the interior of the ceramic tube as a heating wire, and welding it together with the ceramic tube to the base to make a gas sensor;
[0023] Among them, the power of the drying lamp is 40-60W, the temperature is 50-80℃, and the irradiation distance is 20-30cm.
[0024] The stirring rate of steps (2-4) and (8-9) is 200-1000 rpm;
[0025] The heating rate in step (10) is 2-5°C / min.
[0026] The material mainly presents hexagonal nanosheets, with a side length of 1.1 to 1.6 μm and a thickness of 80 to 130 nm. Au nanoparticles are uniformly loaded on the surface of the Zn2SnO4 / SnO2 / ZnO composite material, wherein the loading amount of Au is 0.4 to 3 wt%;
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The present invention uses anhydrous ethanol and deionized water as solvents, zinc acetate and tin tetrachloride as precursors, sodium citrate as a surfactant, and sodium hydroxide as a precipitant to prepare a Zn2SnO4 / SnO2 / ZnO composite material with a heterogeneous structure through a one-step hydrothermal method; sodium borohydride is used as a reducing agent, and a trace amount of precious metal Au is uniformly loaded on the surface of the material through an impregnation method; the production process is simple and the cycle is short.
[0029] (2) The Au-loaded Zn2SnO4 / SnO2 / ZnO composite material prepared by the present invention greatly improves the sensitivity of the gas sensor by virtue of the heterogeneous structure and the noble metal loading, and has excellent sensitivity and selectivity to TEA. At the optimal working temperature of 300°C, the sensitivity to 100ppm TEA is 60-120. The gas sensor using the composite material has a detection limit of 0.5ppm for TEA, and within the working temperature range of 100-350°C, the response time to a concentration of 100ppm TEA is less than 1s, and the recovery time is 4-750s.
[0030] (3) The preparation cost of the present invention is low, and it is suitable for mass production. The prepared triethylamine gas sensor has a wide working range and has important application value. Description of the drawings:
[0031] Figure 1 Shown is a schematic diagram of the structure of the sensor in the present invention;
[0032] Among them, 1-resistance wire, 2-ceramic tube, 3-metal electrode, 4-sensitive material, 5-platinum wire, 6-base;
[0033] Figure 2 Shown is a scanning electron microscope photograph of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material obtained in Example 1;
[0034] Figure 3 Shown is the sensitivity diagram of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material obtained in Example 1 to 100 ppm of different gases at different working temperatures;
[0035] Figure 4 Shown is the sensitivity diagram of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material obtained in Example 2 to 100 ppm of different gases at different working temperatures;
[0036] Figure 5 Shown is a single response curve of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material obtained in Example 2 to 100 ppm TEA at 300°C;
[0037] Figure 6 Shown is the sensitivity diagram of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material obtained in Example 3 to 100 ppm of different gases at different working temperatures;
[0038] Figure 7 The composite materials obtained in Comparative Example 1 and Examples 1 to 3 are shown as response curves to different concentrations of TEA at their optimal working temperatures (350° C. for Comparative Example 1 and 300° C. for Examples 1 to 3); Specific implementation method:
[0039] Au-loaded Zn2SnO4 / SnO2 / ZnO thin film was prepared on the surface of Al2O3 ceramic tube by hydrothermal method and impregnation method, and appropriate process parameters (such as reaction temperature, reaction time, load ratio, etc.) were selected. A heating coil was built into the Al2O3 ceramic tube to heat the Al2O3 ceramic tube. The electrodes led out from the heating wire and the platinum wire on the Au-loaded Zn2SnO4 / SnO2 / ZnO film were connected to the lead-out circuit and the test circuit respectively, and the presence of the test gas was determined by the change of its resistance with the concentration of the test gas in the environment. The gas sensor showed high selectivity, high sensitivity and short response / recovery time for triethylamine.
[0040] Sensitivity test method: The working temperature of the sensor is adjusted by changing the current of the heating coil, and the resistance value (R a ) and the resistance value (R g ) can be used to obtain the sensitivity of the sensor. The sensitivity of the sensor to triethylamine is defined as S = R a / R g Through the characteristic curve of sensitivity to gas concentration, the unknown triethylamine gas concentration can be detected. The test environment is temperature: 28±2℃, relative humidity: 40±5%RH. The test gas is the volatile gas corresponding to volatile organic compounds (triethylamine, ethanol, methanol, acetone, toluene and ammonia).
[0041] The present invention prepares an oxide semiconductor gas sensor that is sensitive to triethylamine, and can detect the presence and concentration of triethylamine in a variety of mixed gases by adjusting the working temperature. The gas sensor has low preparation cost and has excellent properties such as high selectivity, high sensitivity and fast response recovery characteristics.
[0042] Comparative Example 1:
[0043] (1) Dissolve 2 mmol Zn(CH3COO)2·2H2O and 1 mmol C6H5Na3O7·2H2O in 10 mL deionized water and stir for 10 min to obtain solution A;
[0044] (2) Dissolve 1 mmol SnCl4·5H2O in 5 mL anhydrous ethanol and stir for 5 min to obtain solution B;
[0045] (3) Under magnetic stirring, solution A and solution B were mixed and stirred for 10 min to obtain solution C;
[0046] (4) Dissolve 10 mmol NaOH in 25 mL deionized water, add dropwise to solution C, and stir thoroughly for 30 min; the stirring rate in steps (1 to 4) is 800 rpm;
[0047] (5) The solution obtained in step (4) was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, sealed, and kept in an oven at 180° C. for 16 h. After naturally cooling to room temperature, it was washed alternately with deionized water and anhydrous ethanol for 6 times, and then dried at 60° C. for 4 h to obtain a powder material;
[0048] (6) annealing the material obtained in step (5) at 800° C. for 0.5 h at a heating rate of 5° C. / min, and then naturally cooling to room temperature to obtain a Zn2SnO4 / SnO2 / ZnO composite material;
[0049] (7) The gas-sensitive material obtained in step (6) is prepared into a paste with deionized water and evenly coated on the surface of the ceramic tube; wherein the coating thickness is 15 μm and the solid-liquid ratio is 10 mg:20 μL;
[0050] (8) The ceramic tube coated with the gas-sensitive material is placed under a rapid drying lamp for 5 minutes, and after drying, is placed in a muffle furnace and annealed at 800°C for 0.5 hours with a heating rate of 5°C / min, and then naturally cooled to room temperature. The power of the rapid drying lamp is 50W, the temperature is 60°C, and the irradiation distance is 25cm. A nickel-chromium alloy heating coil with a resistance value of 32Ω is passed through the inside of the ceramic tube as a heating wire, and is welded to the base together with the ceramic tube to make a indirectly heated gas sensor, but is not limited to indirectly heated gas sensors. Its structure is as follows Figure 1 As shown;
[0051] (9) The gas sensor was aged on an aging table for 48 hours at a temperature of 28°C and a relative humidity of 40%RH. The gas sensing characteristics of the gas sensor were tested using a static test system (FLUKE).
[0052] Embodiment 1:
[0053] (1) Dissolve 2 mmol Zn(CH3COO)2·2H2O and 1 mmol C6H5Na3O7·2H2O in 10 mL deionized water and stir for 10 min to obtain solution A;
[0054] (2) Dissolve 1 mmol SnCl4·5H2O in 5 mL anhydrous ethanol and stir for 5 min to obtain solution B;
[0055] (3) Under magnetic stirring, solution A and solution B were mixed and stirred for 10 min to obtain solution C;
[0056] (4) Dissolve 10 mmol NaOH in 25 mL deionized water, add dropwise to solution C, and stir thoroughly for 30 min; wherein the stirring rate of steps (1 to 4) is 800 rpm;
[0057] (5) The solution obtained in step (4) was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, sealed, and kept in an oven at 180° C. for 16 h. After naturally cooling to room temperature, it was washed alternately with deionized water and anhydrous ethanol for 6 times, and then dried at 60° C. for 4 h to obtain a powder material;
[0058] (6) annealing the material obtained in step (5) at 800° C. for 0.5 h at a heating rate of 5° C. / min, and then naturally cooling to room temperature to obtain a Zn2SnO4 / SnO2 / ZnO composite material;
[0059] (7) 30 mg of the product obtained in step (6) was added to 15 mL of deionized water, and then ultrasonicated at a power of 200 W for 10 min to obtain a reaction solution;
[0060] (8) adding 15 μL of 0.02 g / mL chloroauric acid solution to the solution of step (7), and stirring magnetically for 10 min at a stirring rate of 400 rpm;
[0061] (9) adding 400 μL of 0.02 mol / L sodium borohydride solution to the solution of step (8), stirring for 4 h, washing with deionized water and anhydrous ethanol alternately for 4 times, and then drying at 60° C. for 4 h to obtain a powder material, wherein the stirring speed is 400 rpm;
[0062] (10) placing the material obtained in step (9) in a muffle furnace, annealing at 450° C. for 2 h at a heating rate of 2° C. / min, and then naturally cooling to room temperature to obtain an Au-loaded Zn2SnO4 / SnO2 / ZnO composite material;
[0063] (11) The gas-sensitive material obtained in step (10) is prepared into a paste with deionized water and evenly coated on the surface of the ceramic tube; wherein the coating thickness is 15 μm and the solid-liquid ratio is 10 mg:20 μL;
[0064] (12) The ceramic tube coated with the gas-sensitive material is placed under a rapid drying lamp for 5 minutes, and after drying, is placed in a muffle furnace and annealed at 450°C for 2 hours with a heating rate of 2°C / min, and then naturally cooled to room temperature. The power of the rapid drying lamp is 50W, the temperature is 60°C, and the irradiation distance is 25cm. A nickel-chromium alloy heating coil with a resistance value of 32Ω is passed through the inside of the ceramic tube as a heating wire, and is welded to the base together with the ceramic tube to make a indirectly heated gas sensor, but is not limited to indirectly heated gas sensors. Its structure is as follows Figure 1 As shown;
[0065] (13) The gas sensor was aged on an aging table for 48 hours at a temperature of 28°C and a relative humidity of 40%RH. The gas sensing characteristics of the gas sensor were tested using a static test system (FLUKE).
[0066] like Figure 2 As shown, the SEM image of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material prepared in this embodiment can be observed, and its morphology is mainly a hexagonal nanosheet structure, with a side length of about 1.3μm and a thickness of about 100nm. A small amount of gold nanoparticles with a diameter of about 10nm are evenly distributed on the surface of the material. The loading amount is about 0.5wt%. Figure 3The figure shows the sensitivity of the material to different gases at 100ppm at different working temperatures. The results show that the gas sensor prepared by the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material has a sensitivity of 66 to 100ppm TEA at a working temperature of 300℃, which has good selectivity and high sensitivity.
[0067] Embodiment 2:
[0068] (1) Dissolve 2 mmol Zn(CH3COO)2·2H2O and 1 mmol C6H5Na3O7·2H2O in 10 mL deionized water and stir for 10 min to obtain solution A;
[0069] (2) Dissolve 1 mmol SnCl4·5H2O in 5 mL anhydrous ethanol and stir for 5 min to obtain solution B;
[0070] (3) Under magnetic stirring, solution A and solution B were mixed and stirred for 10 min to obtain solution C;
[0071] (4) Dissolve 10 mmol NaOH in 25 mL deionized water, add dropwise to solution C, and stir thoroughly for 30 min; wherein the stirring rate of steps (1 to 4) is 800 rpm;
[0072] (5) The solution obtained in step (4) was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, sealed, and kept in an oven at 180° C. for 16 h. After naturally cooling to room temperature, it was washed alternately with deionized water and anhydrous ethanol for 6 times, and then dried at 60° C. for 4 h to obtain a powder material;
[0073] (6) annealing the material obtained in step (5) at 800° C. for 0.5 h at a heating rate of 5° C. / min, and then naturally cooling to room temperature to obtain a Zn2SnO4 / SnO2 / ZnO composite material;
[0074] (7) 30 mg of the product obtained in step (6) was added to 15 mL of deionized water, and then ultrasonicated at a power of 200 W for 10 min to obtain a reaction solution;
[0075] (8) adding 45 μL of 0.02 g / mL chloroauric acid solution to the solution of step (7), and stirring magnetically for 10 min at a stirring rate of 400 rpm;
[0076] (9) adding 400 μL of 0.02 mol / L sodium borohydride solution to the solution of step (8), stirring for 4 h, washing with deionized water and anhydrous ethanol alternately for 4 times, and then drying at 60° C. for 4 h to obtain a powder material, wherein the stirring speed is 400 rpm;
[0077] (10) placing the material obtained in step (9) in a muffle furnace, annealing at 450° C. for 2 h at a heating rate of 2° C. / min, and then naturally cooling to room temperature to obtain an Au-loaded Zn2SnO4 / SnO2 / ZnO composite material;
[0078] (11) The gas-sensitive material obtained in step (10) is prepared into a paste with deionized water and evenly coated on the surface of the ceramic tube; wherein the coating thickness is 15 μm and the solid-liquid ratio is 10 mg:20 μL;
[0079] (12) The ceramic tube coated with the gas-sensitive material is placed under a rapid drying lamp for 5 minutes, and after drying, is placed in a muffle furnace and annealed at 450°C for 2 hours with a heating rate of 2°C / min, and then naturally cooled to room temperature. The power of the rapid drying lamp is 50W, the temperature is 60°C, and the irradiation distance is 25cm. A nickel-chromium alloy heating coil with a resistance value of 32Ω is passed through the inside of the ceramic tube as a heating wire, and is welded to the base together with the ceramic tube to make a indirectly heated gas sensor, but is not limited to indirectly heated gas sensors. Its structure is as follows Figure 1 As shown;
[0080] (13) The gas sensor was aged on an aging table for 48 hours at a temperature of 28°C and a relative humidity of 40%RH. The gas sensing characteristics of the gas sensor were tested using a static test system (FLUKE).
[0081] like Figure 4 As shown in the figure, the sensitivity of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material prepared in this example to different gases at 100ppm at different working temperatures. The results show that the gas sensor prepared by the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material has a sensitivity of 116 to 100ppm TEA at a working temperature of 300℃, which has good selectivity and high sensitivity. Figure 5 The figure shows the single response curve of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material prepared in this example to 100ppm TEA at 300°C. The results show that the response and recovery time of the material to 100ppm TEA at 300°C are <1s and 48s respectively, showing fast response / recovery characteristics.
[0082] Embodiment 3:
[0083] (1) Dissolve 2 mmol Zn(CH3COO)2·2H2O and 1 mmol C6H5Na3O7·2H2O in 10 mL deionized water and stir for 10 min to obtain solution A;
[0084] (2) Dissolve 1 mmol SnCl4·5H2O in 5 mL anhydrous ethanol and stir for 5 min to obtain solution B;
[0085] (3) Under magnetic stirring, solution A and solution B were mixed and stirred for 10 min to obtain solution C;
[0086] (4) Dissolve 10 mmol NaOH in 25 mL deionized water, add dropwise to solution C, and stir thoroughly for 30 min; wherein the stirring rate of steps (1 to 4) is 800 rpm;
[0087] (5) The solution obtained in step (4) was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, sealed, and kept in an oven at 180° C. for 16 h. After naturally cooling to room temperature, it was washed alternately with deionized water and anhydrous ethanol for 6 times, and then dried at 60° C. for 4 h to obtain a powder material;
[0088] (6) annealing the material obtained in step (5) at 800° C. for 0.5 h at a heating rate of 5° C. / min, and then naturally cooling to room temperature to obtain a Zn2SnO4 / SnO2 / ZnO composite material;
[0089] (7) 30 mg of the product obtained in step (6) was added to 15 mL of deionized water, and then ultrasonicated at a power of 200 W for 10 min to obtain a reaction solution;
[0090] (8) adding 75 μL of 0.02 g / mL chloroauric acid solution to the solution of step (7), and stirring magnetically for 10 min at a stirring rate of 400 rpm;
[0091] (9) adding 400 μL of 0.02 mol / L sodium borohydride solution to the solution of step (8), stirring for 4 h, washing with deionized water and anhydrous ethanol alternately for 4 times, and then drying at 60° C. for 4 h to obtain a powder material, wherein the stirring speed is 400 rpm;
[0092] (10) placing the material obtained in step (9) in a muffle furnace, annealing at 450° C. for 2 h at a heating rate of 2° C. / min, and then naturally cooling to room temperature to obtain an Au-loaded Zn2SnO4 / SnO2 / ZnO composite material;
[0093] (11) The gas-sensitive material obtained in step (10) is prepared into a paste with deionized water and evenly coated on the surface of the ceramic tube; wherein the coating thickness is 15 μm and the solid-liquid ratio is 10 mg:20 μL;
[0094] (12) The ceramic tube coated with the gas-sensitive material is placed under a rapid drying lamp for 5 minutes, and after drying, is placed in a muffle furnace and annealed at 450°C for 2 hours with a heating rate of 2°C / min, and then naturally cooled to room temperature. The power of the rapid drying lamp is 50W, the temperature is 60°C, and the irradiation distance is 25cm. A nickel-chromium alloy heating coil with a resistance value of 32Ω is passed through the inside of the ceramic tube as a heating wire, and is welded to the base together with the ceramic tube to make a indirectly heated gas sensor, but is not limited to indirectly heated gas sensors. Its structure is as follows Figure 1 As shown;
[0095] (13) The gas sensor was aged on an aging table for 48 hours at a temperature of 28°C and a relative humidity of 40%RH. The gas sensing characteristics of the gas sensor were tested using a static test system (FLUKE).
[0096] like Figure 6 As shown in the figure, the sensitivity of the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material prepared in this example to different gases at 100ppm at different working temperatures. The results show that the gas sensor prepared by the Au-loaded Zn2SnO4 / SnO2 / ZnO composite material has a sensitivity of 66 to 100ppm TEA at a working temperature of 300℃, which has good selectivity and high sensitivity. Figure 7 The response curves of the composite materials obtained in Comparative Example 1 and Examples 1 to 3 to different concentrations of TEA at their optimal operating temperatures (350°C for Comparative Example 1 and 300°C for Examples 1 to 3) show that the detection limits of Examples 1 to 3 are all 0.5 ppm, and the material prepared in Example 2 has the highest sensitivity.
[0097] Embodiment 4:
[0098] (1) Dissolve 2 mmol Zn(CH3COO)2·2H2O and 1 mmol C6H5Na3O7·2H2O in 10 mL deionized water and stir for 10 min to obtain solution A;
[0099] (2) Dissolve 1 mmol SnCl4·5H2O in 5 mL anhydrous ethanol and stir for 5 min to obtain solution B;
[0100] (3) Under magnetic stirring, solution A and solution B were mixed and stirred for 10 min to obtain solution C;
[0101] (4) Dissolve 10 mmol NaOH in 25 mL deionized water, add dropwise to solution C, and stir thoroughly for 30 min; wherein the stirring rate of steps (1 to 4) is 800 rpm;
[0102] (5) The solution obtained in step (4) was transferred to a 50 mL stainless steel autoclave lined with polytetrafluoroethylene, sealed, and kept in an oven at 180° C. for 16 h. After naturally cooling to room temperature, it was washed alternately with deionized water and anhydrous ethanol for 6 times, and then dried at 60° C. for 4 h to obtain a powder material;
[0103] (6) annealing the material obtained in step (5) at 800° C. for 0.5 h at a heating rate of 5° C. / min to obtain a Zn2SnO4 / SnO2 / ZnO composite material;
[0104] (7) 30 mg of the product obtained in step (6) was added to 15 mL of deionized water, and then ultrasonicated at a power of 200 W for 10 min to obtain a reaction solution;
[0105] (8) adding 30 μL of 0.02 g / mL chloroauric acid solution to the solution of step (7), and stirring magnetically for 10 min at a stirring rate of 400 rpm;
[0106] (9) The solution obtained in step (8) was washed with deionized water and anhydrous ethanol alternately for 4 times, and then dried at 60° C. for 4 h to obtain a powder material, wherein the stirring speed was 400 rpm;
[0107] (10) annealing the material obtained in step (9) at 450° C. for 2 h at a heating rate of 2° C. / min;
[0108] (11) The gas-sensitive material obtained in step (10) is prepared into a paste with deionized water and evenly coated on the surface of the ceramic tube; wherein the coating thickness is 15 μm and the solid-liquid ratio is 10 mg:20 μL;
[0109] (12) The ceramic tube coated with the gas-sensitive material is placed under a rapid drying lamp for 5 minutes, and then annealed at 800°C for 0.5 hours, with a heating rate of 5°C / min; then a nickel-chromium alloy heating coil with a resistance value of 32Ω is passed through the interior of the ceramic tube as a heating wire, and is welded to the base together with the ceramic tube to make a indirectly heated gas sensor, but not limited to indirectly heated gas sensors. The power of the rapid drying lamp is 50W, the temperature is 60°C, and the irradiation distance is 25cm.
[0110] (13) The gas sensor was aged on an aging table for 48 hours at a temperature of 28°C and a relative humidity of 40%RH. The gas sensing characteristics of the gas sensor were tested using a static test system (FLUKE).
[0111] The result was a failure because sodium borohydride was not added, resulting in the failure of chloroauric acid to be reduced and ultimately the failure to form Au-loaded zinc tin oxide gas-sensitive material.
[0112] In summary, the gas sensor prepared by the Au-loaded zinc-tin oxide composite material has good sensitivity to triethylamine (i.e., Examples 1 to 3). Compared with the gas sensor prepared by a single zinc-tin oxide composite material (Comparative Example 1), it has the advantages of short response time, good selectivity, high sensitivity, and low detection limit; while the zinc-tin oxide that was not successfully loaded with Au (Example 4) did not improve the gas-sensing performance of the sensor.
[0113] The above embodiments are for illustration only and are not intended to be limiting. Any equivalent modifications or changes made thereto without departing from the spirit and scope of the present invention shall be included in the scope of the claims of this application.
[0114] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing an Au-loaded zinc-tin oxide composite triethylamine gas sensor, characterized in that the method comprises the following steps: (1) Add Zn(CH3COO)2·2H2O and C6H5Na3O7·2H2O to deionized water and stir for 5-10 min to obtain solution A. in, The molar ratio is Zn(CH3COO)2·2H2O:C6H5Na3O7·2H2O=1:0.5-1; 1-3 mmol Zn(CH3COO)2·2H2O is added to every 8-12 mL of deionized water; (2) Dissolve SnCl4·5H2O in anhydrous ethanol and stir for 5-10 min to obtain solution B; add 0.5-1.5 mmol SnCl4·5H2O for every 4-6 mL of anhydrous ethanol; (3) under the action of magnetic stirring, solution A and solution B are mixed and stirred for 10 to 20 minutes to obtain solution C; wherein the molar ratio of Zn(CH3COO)2·2H2O to SnCl4·5H2O is 2:1 to 3; (4) dropping NaOH solution into solution C and stirring for 20 to 50 minutes; wherein the molar ratio of NaOH to Zn(CH3COO)2·2H2O and SnCl4·5H2O is 6 to 10:2:1 to 3; (5) transferring the solution obtained in step (4) into a stainless steel autoclave lined with polytetrafluoroethylene, sealing it, keeping it in an oven at 180-200° C. for 14-18 hours, cooling it naturally to room temperature, washing it alternately with deionized water and anhydrous ethanol, and then drying it at 60-80° C. for 3-10 hours to obtain a powder material; (6) annealing the material obtained in step (5) at 600-800° C. for 0.5-2 h, and then naturally cooling to room temperature to obtain a Zn2SnO4 / SnO2 / ZnO composite material; (7) adding the Zn2SnO4 / SnO2 / ZnO composite material to deionized water, and then ultrasonicating at a power of 200 to 300 W for 8 to 15 minutes to obtain a reaction solution; adding 25 to 50 mg of the Zn2SnO4 / SnO2 / ZnO composite material to every 10 to 20 mL of deionized water; (8) adding chloroauric acid solution to the solution of step (7) and stirring magnetically for 8 to 15 minutes; Wherein, the mass ratio of chloroauric acid to the Zn2SnO4 / SnO2 / ZnO composite material contained in step (7) is 1:10-200; The concentration of the chloroauric acid solution is 0.015-0.025 g / mL; (9) adding the sodium borohydride solution to the solution of step (8), stirring for 2 to 5 hours, washing with deionized water and anhydrous ethanol alternately, and then drying at 60 to 80° C. for 3 to 10 hours; wherein the molar ratio of sodium borohydride to chloroauric acid is 1 to 15:1; (10) placing the material obtained in step (9) in a muffle furnace, heating to 350-500° C. for annealing for 1-3 h, and then naturally cooling to room temperature to obtain an Au-loaded Zn2SnO4 / SnO2 / ZnO composite material; (11) The composite material obtained in step (10) is prepared into a paste with deionized water and coated on the surface of the ceramic tube; wherein the coating thickness is 10 to 20 μm and the solid-liquid ratio is 8 to 12 mg:20 μL; (12) The ceramic tube coated with the gas-sensitive material is dried and placed in a muffle furnace, heated to 350-800°C and annealed for 0.5-2h, and then naturally cooled to room temperature; a nickel-chromium alloy heating coil with a resistance value of 30-40Ω is passed through the interior of the ceramic tube as a heating wire, and is welded to the base together with the ceramic tube to make a gas sensor.
2. The method for preparing the Au-loaded zinc-tin oxide composite triethylamine gas sensor according to claim 1, characterized in that The drying in step (12) is performed under a drying lamp for 5 to 10 minutes; the power of the drying lamp is 40 to 60 W, the temperature is 50 to 80° C., and the irradiation distance is 20 to 30 cm.
3. The method for preparing the Au-loaded zinc-tin oxide composite triethylamine gas sensor according to claim 1, characterized in that The stirring rate of steps (2) to (4) and (8) to (9) is 200 to 1000 rpm.
4. The method for preparing the Au-loaded zinc-tin oxide composite material triethylamine gas sensor as claimed in claim 1, characterized in that the heating rate in steps (6), (10) and (12) is 2 to 5°C / min.
5. The method for preparing the Au-loaded zinc-tin oxide composite triethylamine gas sensor according to claim 1, wherein each 20 to 30 mL of NaOH solution in step (4) contains 5 to 15 mmol NaOH.
6. The method for preparing the Au-loaded zinc-tin oxide composite triethylamine gas sensor according to claim 1, characterized in that The material obtained in step (10) is in the form of hexagonal nanosheets with a side length of 1.1 to 1.6 μm and a thickness of 80 to 130 nm. Au nanoparticles are loaded on the surface of the Zn2SnO4 / SnO2 / ZnO composite material, wherein the loading amount of Au is 0.4 to 3 wt%.
Citation Information
Patent Citations
Fusiform zinc oxide gas-sensitive material with high sensitivity to triethylamine
CN107367527A
An Au@ZnO core-shell heterojunction type triethylamine gas-sensitive sensor modified with boron-doped graphene and a preparing method thereof
CN108931559A